2012
DOI: 10.1029/2011jg001827
|View full text |Cite
|
Sign up to set email alerts
|

Effects of forestry operations on dissolved organic carbon concentrations and export in boreal first‐order streams

Abstract: [1] The purpose of this study was to quantify the effects of clear-cutting and site preparation on dissolved organic carbon (DOC) concentrations and export in four boreal headwater streams in northern Sweden. The data set included intensive stream water monitoring from 2 years of pretreatment conditions (2004)(2005), a 2 year post-clear-cut period (2006)(2007), and a 2 year period after site preparation (2008)(2009). To investigate differences in [DOC], an analysis of variance on ranks was performed on the dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
143
4
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 115 publications
(154 citation statements)
references
References 90 publications
6
143
4
1
Order By: Relevance
“…In addition, increased soil temperatures following clear-cutting accelerate mineralization and nitrification in the soil (Paavolainen and Smolander 1998;Smolander et al 2001) and nutrients are released from decomposing logging residues (Palviainen et al 2004). Clear-cutting may also increase total or dissolved organic carbon (TOC, DOC) export (Lamontagne et al 2000;Schelker et al 2012Schelker et al , 2014, which have implications for catchment carbon budgets (Schelker et al 2012), the structure of aquatic food webs (Jansson et al 2000), the acid-base chemistry of surface waters (Buffam et al 2008), and the mobility, toxicity, and bioavailability of trace metals and organic pollutants (Porvari et al 2003;Bergknut et al 2011). The impacts on water quality are long-term and they are generally at its greatest during the first years after clear-cutting (Rosén et al 1996;Ahtiainen and Huttunen 1999;Palviainen et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, increased soil temperatures following clear-cutting accelerate mineralization and nitrification in the soil (Paavolainen and Smolander 1998;Smolander et al 2001) and nutrients are released from decomposing logging residues (Palviainen et al 2004). Clear-cutting may also increase total or dissolved organic carbon (TOC, DOC) export (Lamontagne et al 2000;Schelker et al 2012Schelker et al , 2014, which have implications for catchment carbon budgets (Schelker et al 2012), the structure of aquatic food webs (Jansson et al 2000), the acid-base chemistry of surface waters (Buffam et al 2008), and the mobility, toxicity, and bioavailability of trace metals and organic pollutants (Porvari et al 2003;Bergknut et al 2011). The impacts on water quality are long-term and they are generally at its greatest during the first years after clear-cutting (Rosén et al 1996;Ahtiainen and Huttunen 1999;Palviainen et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In a study of a highly modified German peatland, Frank et al (2014) Nieminen, 2004;Schelker et al, 2012;Nieminen et al, 2014). Within semi-natural peatlands, Clay et al (2012) measured higher DOC concentrations in an eroded compared to a natural peat catchment, and some studies have suggested that moorland burning may enhance DOC loss rates (e.g.…”
Section: Effects Of Peatland Drainage and Rewetting On Doc Fluxesmentioning
confidence: 99%
“…The absence of this parameter in most field sampling datasets (Caruso et al 2008) may greatly increase the prediction uncertainties associated with the transport and fate of metals. Several studies (Schelker et al 2012;Raymond and Saiers 2010) have shown that DOC concentrations can fluctuate up to several hundreds of per cent due to land use changes (e.g. deforestation), storm events and seasonal variability.…”
Section: Metals Governed By Equilibrium Processesmentioning
confidence: 99%